PEACE in the midst of an emergency: a rash not to miss. Issue 11 (3rd November 2020) - Stavrou, Christiana; Mackenzie, Strachan; Pocock, Rachael; Wilson, Andrew J
Abstract : We present the case of a 29-year-old woman who initially presented to her GP with a short history of non-pruritic annular skin lesions with central clearing. A month later, she developed signs and symptoms of bone marrow failure with bruising, epistaxis and fatigue. After urgent review of a blood film, she was diagnosed with acute promyelocytic leukaemia (APML), which is a haematological emergency. Treatment with all-trans retinoic acid (ATRA) was commenced immediately and she was subsequently treated with arsenic trioxide (ATO). The annular rash was subsequently diagnosed as paraneoplastic erythema annulare centrifugum (PEACE), which resolved with treatment. This case demonstrates the importance of the urgent diagnosis of APML and highlights PEACE as a rash that clinicians should be aware of, as it can be the initial manifestation of a number of both haematological and non-haematological malignancies.